Optimization of medium formulation for folate biosynthesis by Lactobacillus plantarum I-UL4 using response surface methodology - Muhamad Nor, Norfarina (2011)
Folate plays an important role in human life as one of the most important components for the synthesis of purine, guanine, adenine, pyrimidine and thymine. In this study, lactic acid bacteria (Lactococcus lactis NZ 9000 and MG 1363, Lactobacillus plantarum I-UL4, and Lactobacillus johnsonii DSM 20553) were investigated for the biosynthesis of folate. The total folate concentrations in lactic acid bacteria were determined by microbiological assay as a reliable method to evaluate the folate level and Lactobacillus rhamnosus (Lactobacillus casei, ATCC 7469) was used to analyze total folate and responds to most native folates. From this study, all lactic acid bacteria able to synthesized folate and Lb. plantarum I-UL4 exhibited as the best folate biosynthesis and used throughout investigation on the medium optimization. Five components of medium composition (carbon source, lactose, nitrogen source, meat extract and p-aminobenzoic acid (PABA)) were optimized conventionally and the cultivation process was conducted in shake-flask experiment. From the investigation, lactose, meat extract and PABA at concentration 20 g/L, 15 g/L and 10 μM respectively gave significant effect towards growth of Lb. plantarum I-UL4 and folate biosynthesis. Thus, these three concentrations were subsequently used for further medium optimization study based on response surface methodology (RSM). Through RSM approach, twenty experiments of three factors in response to folate biosynthesis were carried out. Estimated optimize conditions of the factors for the growth of Lb. plantarum I-UL4 and folate biosynthesis as suggested by RSM are as follows: lactose, 20 g/L; meat extract, 16.57 g/L and PABA concentration, 10 μM. The optimized medium composition was then further applied in the cultivation process using 2 L stirred tank bioreactor. Finally, about 61.89 μg/L of folate was synthesized by Lb.plantarum I-UL4 using the bioreactor, which was slightly higher than in shake-flask experiment (59.88 μg/L) using the optimized medium composition. In a conclusion, a better understanding of the relationship among the factors was obtained by RSM, which was used as a statistical tool to improve the folate biosynthesis of Lb. plantarum I-UL4 in small and large scale cultivation.